RETHINKING HARDOWN HILL: OUR WESTERNMOST EARLY ANGLO-SAXON CEMETERY?. (1st July 2014) - Austin, Matthew
Abstract : This paper reassesses the early Anglo-Saxon assemblage from Hardown Hill, Dorset. Wingrave excavated the objects in 1916 but apart from his 1931 report, and Evison's 1968 analysis, there has been little subsequent discussion. Despite a lack of human remains, the assemblage has been interpreted as representing an early Anglo-Saxon cemetery – our westernmost burial site by a considerable distance and one that pre-dates the historically attested seventh-century expansion of Wessex. The following typological reclassification and contextual analysis casts serious doubts on a funerary context. Instead, an alternative interpretation is presented that views the assemblage as a useful collection of metalwork, intended to be reforged and recycled, which was presumably deposited for safekeeping and never retrieved. Such a reinterpretation highlights the need for a critical reappraisal of material from older excavations. It also has implications for our understanding of post-Roman Dorset, and for the distribution of fifth- and sixth-century Anglo-Saxon material culture more broadly . RÉSUMÉ: Cet article réexamine la construction anglo-saxonne très ancienne de Hardown Hill, dans le Dorset. Wingrave a mis au jour des objets en 1916 mais, hormis son rapport de 1931 et l'analyse d'Evison en 1968, il y a eu peu de discussions ultérieures. Malgré l'absence de restes humains, cette construction a été interprétée comme étant un ancien cimetière anglo-saxonne, notre site de funérailles de très loin le plus occidental, qui date d'avant à l'expansion du Wessex duVII e siècle attestée par des sources historiques. La reclassification typologique et l'analyse textuelle suivantes jettent de sérieux doutes sur le contexte funéraire. Au lieu de cela, l'interprétation présentée considère que cette construction est une collection utile d'objets en métal, dans le but de les recycler en les forgeant à nouveau, probablement déposés pour les conserver mais jamais récupérés. Cette nouvelle interprétation souligne la nécessité de réévaluer d'un il critique les objets trouvés dans des fouilles plus anciennes. En outre, elle influence notre compréhension du Dorset post-romain et de la répartition de la culture matérielle anglo-saxonne desV e etVI e siècles de manière générale. ZUSAMMENFASSUNG: In dieser Abhandlung werden die angelsächsischen Funde von Hardown Hill, Dorset, neu bewertet. Wingrave brachte die Gegenstände 1916 zutage, aber außer seinem Bericht von 1931 und Evisons Analyse von 1968 wurde dieses Thema in der Folge nur wenig behandelt. Trotz des Fehlens menschlicher Überreste wurde der Fundplatz als ein frühes angelsächsisches Gräberfeld interpretiert, und zwar nicht nur die bei weitem westlichste Grabstätte, sondern auch als eine, die der historisch belegten Erweiterung von Wessex im 7. Jahrhundert zeitlich vorangeht. Die nachfolgende typologische Neuklassifizierung und Kontextanalyse stellt jedoch einen Begräbniskontext stark in Zweifel. Stattdessen wird eine alternative Interpretation präsentiert, wonach die Funde als eine nützliche Sammlung von Metallteilen anzusehen ist, die später neu gestaltet oder recycelt werden sollten und die wahrscheinlich zur sicheren Verwahrung hier aufbewahrt, aber nie geborgen wurden. Eine derartige Neuinterpretation verweist auf die Notwendigkeit einer kritischen Neubewertung des Materials aus älteren Ausgrabungen. Des Weiteren hat dies Auswirkungen auf unser Verständnis von Dorset in nachrömischer Zeit und von der Verbreitung der angelsächsischen Sachkultur des 5. und 6. Jahrhunderts ganz allgemein.